(untitled) (2015)
Ubiquitous Computing (UC) is a paradigm in which stakeholders interact with machines in a natural way, without constraints of time, place or access medium. Data is available everywhere to be read, consulted and modified if needed. Thus, UC becomes a powerful tool for industrial applications, where a plenty of sensors, actuators and controllers are integrated in order to produce outcomes efficiently. Nevertheless, it is common to find a lot of communication schemes that use proprietary protocols, so it is difficult to connect those different devices. Furthermore, some Information Systems inside companies are not able to transmit data outside their own networks into Internet. This work aims to show a study case where UC device is designed and implemented in a power generation plant, sensing level of combustible tanks. A System on Chip platform is used to provide flexibility, usability, better performance, better energy management and integration capabilities.